ACUTE RENAL FAILURE ASSOCIATED WITH MALARIA - Manan, Junejo Abdul; Ali, Hassan; Lal, Manohar (Journal of Ayub Medical College Abbottabad, 2006)
Background: Malaria has protean clinical manifestations and acute renal failure (ARF) is one of its serious complications and could be life threatening. This study was carried out to describe the clinical characteristics and factors associated with adverse out come in patients with malarialacute renal failure. Materials and Methods : Data of 46 Patients with ARF and smear positive malaria was analyzed further among all cases of ARF presented to us at Nephrology department of Jinnah Postgraduate Medical Centre, Karachi from January 2003 to December 2004.Results were expressed as mean, standard deviation and range. Results: Among 237 patients with ARF of diverse etiology, 46(19.4%) developed ARF due to falciparum malaria. The male to female ratio was 3.6:1. Oliguria was seen in 76.09% on admission, and 78.26% required dialysis. In addition to ARF, most of the patients had at least one other manifestation of severe malaria. 35(76.06%) patients recovered completely while 11(23.91%) died in early dialysis. Prolonged disease duration, severe ARF, cerebral malaria, hyperbilirubinaemia, and disseminated intravascular coagulopathy (DIC) were poor prognostic factors. Conclusion: Falciparum malaria associated with ARF is a life threatening condition, but early presentation and intervention with appropriate anti-malarial and dialysis therapy is associated with improved survival and recovery of renal function. Early dialysis treatment in patients with severe falcipaum malaria and signs of deteriorating renal function is recommended. Key words: Acute renal failure , malaria, falciparum malaria, haemodialysis .